Inclusive Language in Spanish as Interpellation to Educational Authorities. (12th May 2019) - Banegas, Darío Luis; López, María Fernanda
Abstract: The aim of this commentary is to discuss and promote discussion on some linguistic and pedagogical issues around the use of gender inclusive language, particularly the - e morpheme in plural forms, in Spanish. Its speakers are experiencing and becoming aware of language change in real time concerning the use of morphosyntactic choices that seek embrace gender equality, diversity, representation, and diversity. This language change impacts directly on formal education and educational administrators who are under pressure not only from different social actors but also from their own beliefs on whether they should promote, ignore, or mitigate the linguistic changes that society is producing through their situated practices. Against this background, to what extent are educational authorities professionally prepared to encourage academic discussions on inclusive language in education? How can applied linguists help? Having these questions as our Southern Cross, our commentary lies at the intersection of language change and educational authorities' professional knowledge.